Effects of the Rhizosphere fungus Cunninghamella bertholletiae on the Solanum lycopersicum response to diverse abiotic stresses - Kazerooni, Elham Ahmed; Mohammed Al-Sadi, Abdullah; Rashid, Umer; Kang, Sang Mo; Kim, Il-Doo; Lee, In Jung (Multidisciplinary Digital Publishing Institute, 2022)
This study examined the efficiency of fungal strain (Cunninghamella bertholletiae) isolated from the rhizosphere of Solanum lycopersicum to reduce symptoms of salinity, drought and heavy metal stresses in tomato plants. In vitro evaluation of C. bertholletiae demonstrated its ability to produce indole-3-Acetic Acid (IAA), ammonia and tolerate varied abiotic stresses on solid media. Tomato plants at 33 days’ old, inoculated with or without C. bertholletiae, were treated with 1.5% sodium chloride, 25% polyethylene glycol, 3 mM cadmium and 3 mM lead for 10 days, and the impact of C. bertholletiae on plant performance was investigated. Inoculation with C. bertholletiae enhanced plant biomass and growth attributes in stressed plants. In addition, C. bertholletiae modulated the physiochemical apparatus of stressed plants by raising chlorophyll, carotenoid, glucose, fructose, and sucrose contents, and reducing hydrogen peroxide, protein, lipid metabolism, amino acid, antioxidant activities, and abscisic acid. Gene expression analysis showed enhanced expression of SlCDF3 and SlICS genes and reduced expression of SlACCase, SlAOS, SlGRAS6, SlRBOHD, SlRING1, SlTAF1, and SlZH13 genes following C. bertholletiae application. In conclusion, our study supports the potential of C. bertholletiae as a biofertilizer to reduce plant damage, improve crop endurance and remediation under stress conditions.